PENGARUH ETNOSENTRISME, CITRA MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN BATIK - Firman Fauzi (Universitas Mercu Buana, 2020)
This study aims to analyze the influence of ethnocentrism, brand image and lifestyle on batik purchase decision. Population in this study are consumers in the West Jakarta area. The sample used was 150 respondents, calculated based on the Hair formula. The sampling method of respondent used in this study is through convenience sampling. Data collection methods using survey methods, with the research instrument is a questionnaire. Analysis’s system that used is a statistic analysis as multiple linear regression tests with SPSS version 23 application. The results of this study indicate that partially ethnocentrism and lifestyle have a positive and significant effect on batik purchase decision. While the brand image has a positive effect, but not significantly to the batik purchase decision.